2020
DOI: 10.1186/s40729-020-00245-3
|View full text |Cite
|
Sign up to set email alerts
|

Implant primary stability depending on protocol and insertion mode — an ex vivo study

Abstract: Background: Dental implant primary stability is thought to be a fundamental prerequisite for the long-term survival and success. The aim of this study was to analyze the influence of protocol and insertion mode on dental implant stability ex vivo. One hundred and twenty implants were inserted either manually or machine-driven into porcine mandibles by a standard or over-dimensioned protocol. Dental implant stability was measured via resonance frequency analysis (RFA), insertion torque (IT), and torque out (TO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 33 publications
0
7
0
2
Order By: Relevance
“…Even if the primary stability of dental implants is controversially discussed as a decisive parameter for successful masticatory functional rehabilitation in the context of two-stage loading concepts and oversized drilling protocols are also employed, the development of alternative loading concepts (i.e., transgingival healing, immediate loading) showed the need as well as the importance of primary stability [ 27 ]. It has been repeatedly found in the literature that the final osteotomy position for the preparation of the implant bed should be determined by adapted drilling in order to achieve an individual and variable degree of bone compression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even if the primary stability of dental implants is controversially discussed as a decisive parameter for successful masticatory functional rehabilitation in the context of two-stage loading concepts and oversized drilling protocols are also employed, the development of alternative loading concepts (i.e., transgingival healing, immediate loading) showed the need as well as the importance of primary stability [ 27 ]. It has been repeatedly found in the literature that the final osteotomy position for the preparation of the implant bed should be determined by adapted drilling in order to achieve an individual and variable degree of bone compression [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As already published by our group [ 5 , 26 , 27 ], 15 mandibular bones of fresh porcine cadavers were purchased from a local butcher. According to the butcher, the animals showed no signs of pathological bone conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, primary stability plays a key role in allowing good osseointegration of the implant, thus indirectly determining the long-term outcome of a screw (Javed et al , 2013; Vollmer et al , 2020). According to the literature on osseointegrated devices, which mainly focuses on osseointegration in the oral field, primary stability depends on bone quality (Rues et al , 2021), screw geometrical features (Shah et al , 2012; Redžepagić-Vražalica et al , 2021) and insertion procedure (Staedt et al , 2020). LBV structure is a stochastic porous structure, which was shown to be extremely similar to the trabecular bone structure (Qin et al , 2013); its benefits in long-term osseointegration were demonstrated in Chen et al (2021) and Deering et al (2021).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several devices have been developed to measure implant stability as an indicator of the success of implant treatment. The Osstell® device [ 4 ] allows the measurement of the implant stability quotient (ISQ) using the resonance frequency analysis (RFA) method, whereas the Periotest® device [ 5 ] uses the percussion method. More recently, the AnyCheck® device, which also relies on the percussion method, has been developed [ 6 ].…”
Section: Introductionmentioning
confidence: 99%